PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DIMODERASI DISIPLIN KERJA PADA UPTD DIKPORA KECAMATAN SAYUNG KABUPATEN DEMAK - Bakri, Umar (Students Journal of Economic and Management, 2012)
The purpose of this study to : Examining the effect of motivation on the performance of elementary school teachers in the district Dikpora UPTD Sayung Demak regency.Testing the effect of job satisfaction on the performance of elementary school teachers in the district Dikpora UPTD Sayung Demak regency.Test the effect of labor discipline moderating influence of motivation on the performance of elementary school teachers in the district Dikpora UPTD Sayung Demak regency. Examine the effect of labor discipline moderating influence of job satisfaction on the performance of elementary school teachers in the district Dikpora UPTD Sayung Demak. Research conducted an empirical study to prove the effect of work motivation and job satisfaction on the performance of elementary school teachers working in the discipline moderated Dikpora UPTD Sayung Demak district numbering 343 people scattered in 44 schools. The sampling technique used is proportional random sampling, the samples were taken by 78 teachers, variables studied were the independent variables of work motivation and job satisfaction, namely labor discipline moderating variables and the dependent variable teacher performance. Data analysis techniques in this study using regression analysis and hypothesis testing moderation calculation t test at ignificance level of 5%. The results were obtained: Motivation significant positive effect on teacher performance, obtained significance value of 0.000 is less than 0.05.Job satisfaction significant positive effect on teacher performance, obtained significance value of 0.000 is less than 0.05.Discipline is not working to strengthen the influence of motivation on teacher performance obtained significance value of 0.344 is greater than 0.05.Discipline of work to strengthen the influence of job satisfaction on performance, teachers obtained significance value of 0.621 is greater than 0.05. Keywords: Work motivation, job satisfaction, Work Discipline and Teacher Performance